Surface modification of silica micro-powder by titanate coupling agent and its utilization in PVC based composite. (8th November 2021) - Zhang, Youpeng; Ding, Chong; Zhang, Na; Chen, Chen; Di, Xiangyun; Zhang, Yihe
Graphical abstract: Highlights: The surface of SMP was chemically modified by KTTO successfully. The dispersibility and hydrophobicity of SMP modified by KTTO were improved. KTTO provided a connecting link at the inorganic–organic interface. Mechanical and thermal properties of composites filled with mSMP were enhanced. Abstract: Surface modification of silica micro-powder (SMP) was performed by using commercially available titanate coupling agent KTTO, and polyvinyl chloride (PVC) based composites were prepared by melting and blending PVC and processing aids with SMP before and after modification as fillers. Through XRD, FT-IR, XPS, SEM characterizations and contact angle test, it is determined that the surface of SMP was chemically modified by KTTO successfully. The dispersity of SMP was improved after the KTTO modification treatment although no change was found in the crystal structure of SMP. Moreover, excellent hydrophobicity was achieved by a layer of organic molecules on the surface of modified silica micro-powder (mSMP). The static and dynamic mechanical properties, heat resistance, thermal conductivity, and thermal stability of pure PVC, SMP/PVC, and mSMP/PVC composites with respect to cross-sectional micromorphology were compared. The results indicate that KTTO modification treatment effectively improved the mechanical properties of mSMP/PVC composites, especially increasing the tensile strength and notched impact strength by 43% and 36%, respectively. A significant enhancement of the interfacial bonding between the mSMP filler and PVC matrix was also identified. Furthermore, the thermal conductivity and thermal stability of mSMP/PVC composite were improved by the KTTO modification. The mSMP/PVC composite has a potential application in plates and profiles for construction and buildings.